2020
DOI: 10.1007/s10120-020-01112-1
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel plus S-1 versus cisplatin plus S-1 in unresectable gastric cancer without measurable lesions: a randomized phase II trial (HERBIS-3)

Abstract: Background Cisplatin plus S-1 (CS) is the standard first-line chemotherapy for advanced gastric cancer (AGC) in Japan. A previous phase III trial showed that docetaxel plus S-1 (DS) was effective for AGC without measurable lesions, but no studies have compared these two regimens. Methods Eligible patients had unresectable or recurrent HER2-negative AGC without measurable lesions. Patients were randomized to DS (docetaxel 40 mg/m 2 on day 1, S-1 80-120 mg on days 1-14, every 3 weeks) or CS (cisplatin 60 mg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…It is well known that docetaxel and ABX are very effective for peritoneal metastasis because it has effective transferability to tumor tissues and high antitumor effects for peritoneal metastasis compared with paclitaxel [ 22 – 24 ]. The median OS was 20.0 months with docetaxel and S-1 (DS regimen) and 15.8 months with CS regimen in the phase II HERBIS-3 study [ 25 ]. However, the phase III START trial further showed that the DS regimen only improved OS as 12.5 months compared with S-1 alone as 10.8 months (HR of 0.837, 95%CI 0.711–0.985) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that docetaxel and ABX are very effective for peritoneal metastasis because it has effective transferability to tumor tissues and high antitumor effects for peritoneal metastasis compared with paclitaxel [ 22 – 24 ]. The median OS was 20.0 months with docetaxel and S-1 (DS regimen) and 15.8 months with CS regimen in the phase II HERBIS-3 study [ 25 ]. However, the phase III START trial further showed that the DS regimen only improved OS as 12.5 months compared with S-1 alone as 10.8 months (HR of 0.837, 95%CI 0.711–0.985) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A phase I/II study of docetaxel, cisplatin, and S-1 (DCS regimen) enrolled advanced gastric cancer patients with peritoneal metastasis, which showed high anti-tumor efficacy with an OS of 15.5 months but more frequencies grade of 3 or 4 toxicity [ 16 ] . The HERBIS-3 study reported that the OS of DS regimen was superior to CS regimen in gastric cancer patients with positive peritoneal lavage cytology, with the 2-year OS rates being 70.0% versus 16.7% (HR 0.153, 95% CI 0.037–0.632) [ 25 ]. Thus, the docetaxel-based three agents regimen could improve OS of gastric cancer patients with peritoneal metastasis but more toxicity which limits its use in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The HERBIS-3 trial, a randomized phase II trial in unresectable or recurrent advanced GC, showed that S-1 plus docetaxel (DS) was more effective than cisplatin plus S-1, which had been the standard first-line chemotherapy in Japan. 63 Thus, docetaxel may also be important as…”
Section: Postoperative Adjuvant Chemotherapymentioning
confidence: 99%
“…The results established CAPEOX as another standard adjuvant treatment regimen for stage II/III GC in Asia. The HERBIS‐3 trial, a randomized phase II trial in unresectable or recurrent advanced GC, showed that S‐1 plus docetaxel (DS) was more effective than cisplatin plus S‐1, which had been the standard first‐line chemotherapy in Japan 63 . Thus, docetaxel may also be important as a key drug in the perioperative chemotherapy of GC.…”
Section: Perioperative Treatmentmentioning
confidence: 99%
“…Surgical resection in combination with neoadjuvant/adjuvant chemotherapy, namely, multimodal therapy (Y Kakeji, et al, 2022 ), represents the mainstay of care for treatment of GC; however, tumor recurrence rates can reach 25%–40% in GC patients classified as stages II–IV (American Joint Committee on Cancers; AJCC2) ( Bang, et al, 2012 ; Cristescu, et al, 2015 ; Kim, et al, 2005 ; Lee, et al, 2012 ; Macdonald, et al, 2001 ). Given the poor prognosis of advanced gastric cancer (AGC) patients, development of more effective chemotherapy regimens remains an unmet clinical need (Y Kurokawa, et al, 2021 ), which is also the current research hotspot ( Zhu, et al, 2020 ). To date, fluoropyrimidine plus platinum compounds are the most widely used chemotherapeutic agents against GC worldwide ( Cunningham, et al, 2008 ; Kang, et al, 2009 ; Koizumi, et al, 2008 ; Kurokawa, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%